A digital subtraction radiography based tool for periodontal bone resorption analysis - Schiabel, Homero; Rodrigues, Eveline B.; Rubira-Bullen, Izabel R. F. (Revista Brasileira de Física Médica, 2015)
The aim of this paper was to describe an aided diagnosis scheme for periodontal bone resorption so that the dentist can make an early diagnosis of the periodontal disease and establish the best treatment plan to increase the success of healing. Three ways of displaying the results are provided: qualitative, simple quantitative and colored-percentage quantitative views. A total of 72 pairs of in vitro radiographic images were used. The main procedure registers the images perspective projection aimed to align them in rotation and translation, and is followed by the application of a contrast correction technique. The results from the subtraction were evaluated firstly by the comparison between the actual and the digital sizes corresponding to the holes made by drills in phantoms. The mean error was 4.2%. The method was also applied to actual tooth radiographic images and could detect clearly the effect of treatment of periodontal diseases. It is dependent on the reproducibility of the process of radiographs acquisition and digitization, but the calculated mean error allows to conclude its better efficacy compared to usual procedures in this field.